Effects of aging on colony count and antibiotic susceptibility patterns of Escherichia coli isolated from male Wistar rats - Megantara, Imam; Amira, Putri Alia; Sylviana, Nova (Universa Medicina, 2025)
BackgroundPhysiological and immunological changes in the elderly may contribute to the composition and patterns of the gut microbiota, including Escherichia coli, as well as antimicrobial susceptibility patterns. The research was conducted to assess the effect of aging on Escherichia coli growth and susceptibility to several antibiotics. MethodsAn experimental laboratory study using 7 young (6-month-old) (YWR) and 7 old (24-month-old) Wistar rats (OWR) as subjects. Rat stool specimens were used as representing the subjects. Antibiotic susceptibility was determined using the Kirby-Bauer method. The independent t-test and Mann-Whitney test were used to analyse the data. ResultsAll fecal specimens collected from both groups were positive for E. coli growth. The YWR showed a low density of E. coli, while the OWR showed a statistically significant increase in the population of E. coli (p=0.001). Overall, the E. coli isolates showed a high proportion of resistance to erythromycin (100%), ampicillin (86%), and oxytetracycline (58%). The isolates collected from YWR were significantly more resistant to streptomycin (83% vs. 19%, p<0.001) and tetracycline (47% vs. 3%, p<0.001) than the isolates from OWR. Young Wistar rats also had a higher resistance rate than OWR to the most frequently used antibiotics, such as ampicillin (97% vs. 76%, p<0.001). ConclusionOur study demonstrated an increase in the fecal E. coli population with increasing age of the Wistar rats. In addition, the results of susceptibility tests for several antibiotics showed that age may not be associated with an increase in the population of a resistant strain of E. coli.